The Influence of Caries Infiltrant Combined with and without Conventional Adhesives on Sealing of Sound Enamel (In Vitro Study) - Balasim, Marwa; Al-Dabagh, Dhiaa J (Journal of Baghdad College of Dentistry, 2016)
Background: The formation of white spot lesions around fixed orthodontic attachments is a common complication during and after fixed orthodontic treatment, which hinders the result of a successfully completed orthodontic treatment. The aim of the study was to assess the effectiveness of the Caries Infiltrant (ICON®) on prevention of caries on the smooth enamel surface when applied alone or combined with conventional adhesives. Materials and methods: Seventy eight human premolar enamel discs were randomly assigned to six groups (n=13). The discs were etched and treated with resins of different monomer content forming the following groups: (1)Untreated etched samples served as the negative control, (2) ICON® (DMG), (3) Adper™ SB 2 (3M ESPE), (4) Heliobond (IvoclarVivadent), (5) ICON®+ Adper™ SB 2 and (6) ICON®+ Heliobond. Specimens were subjected to demineralization by immersion in hydrochloric acid (pH 2.6) for 18 days. Calcium dissolution into the acid was assessed by photometric test via spectrophotometer at 24 hour intervals. Results: The results revealed that, there was a highly significant difference between the sealed groups and the unsealed (untreated) one (p≤0.00) indicating that the unsealed specimens showed the highest amount of Ca ion loss among all other groups. Additionally, there was no significant difference between untreated specimens and the ICON® sealed ones. While, Heliobond decreased the Ca ion loss significantly compared to the untreated specimens and Adper™ SB 2 performed significantly better than both ICON® and Heliobond. Furthermore, the combination of ICON® with either Adper™ SB 2 or Heliobond served as the best protective measures and maintained the protective effect during the whole experiment period. Therefore, within the limitations of this in vitro study, it could be concluded that the use of Caries Infiltrant prior to the application of the tested conventional adhesives increases their protective effect against demineralization.